ENTREPRENEURIAL INTENTION DEVELOPMENT MODEL ON STUDENTS - Indra, Kurniawan (STIE PGRI Dewantara Jombang, 2023)
This research aims to determine the effectiveness of entrepreneurship education on students' entrepreneurial intention by placing motivation as a mediating variable.The research used a survey to obtain 308 Indonesian students who had taken entrepreneurship courses. Data analysis uses structural equation model partial least squares (SEM-PLS).The research results state that the effectiveness of entrepreneurship education has a direct effect on motivation. Motivation has an immediate effect on entrepreneurial intentions, while the effectiveness of entrepreneurship education has no direct impact on entrepreneurial intentions, and motivation is a mediating variable. Based on the research results, it implies that a stimulus is needed in the role of lecturers to increase motivation, which can encourage students to be interested in opening a business such as best practice.